Preschoolers' secure base script representations predict teachers' ratings of social competence and externalizing behavior. Issue 3 (4th May 2019) - Fernandes, Marilia; Verissimo, Manuela; Santos, António J.; Fernandes, Carla; Antunes, Marta; Vaughn, Brian E.
ABSTRACT: Recent meta-analyses have reported significant effects of attachment quality on social competence, mostly using observational assessments of attachment behavior to assess security. We analyze the associations between attachment security – assessed as a secure base script, and social competence with peers – measured by teachers' ratings on two self-report instruments, in a Portuguese sample of 82 preschool children (34 boys and 48 girls). We also tested the association between children's secure base script scores and teacher ratings for externalizing and internalizing symptomatology. Results show significant sex differences. Girls had higher scores on secure base script and were rated by teachers as more socially competent, while boys received higher ratings for aggressive/externalizing behaviors. Nonetheless, when the effect of child sex was controlled, attachment representations were positively associated with child social competence and negatively associated with ratings of externalizing behaviors.